A laser irradiation resistant coating composition and coating preparation method
By combining the three-layer structure design of heat insulation, lateral heat dissipation and reflection effects in the coating, the existing coating is solved, and the problem of the improvement of protection indicators brought about by the development of high-energy laser technology is achieved, and efficient anti-high-energy laser radiation performance is achieved.
Patent Information
- Application Number
- CN202411790315.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing reflective and ablation thermal insulation laser protective coatings have their own advantages and disadvantages, and it is difficult to meet the gradually improved protection indicators brought about by the development of high-energy laser technology. How to effectively combine multiple protection mechanisms to improve the protective performance of the coating has become a key technical problem.
An anti-laser radiation coating composition is provided, adopting a three-layer structure, which is distributed in sequence by the insulating layer, the transverse heat dissipation layer and the reflective layer. Through the coordinated reflection, the transverse heat dissipation and the thermal insulation effect, the anti-high-energy laser radiation performance of the coating is improved.
The coating is effectively resistant to high-energy laser radiation. Through the low thermal conductivity of the heat insulation layer, the high thermal conductivity of the transverse heat dissipation layer and the high reflective characteristics of the reflective layer, the laser energy absorption and heat deposition are synergistically prevented, and the protection time of the coating is extended.
Smart Images

Figure CN119264812B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of coating materials and relates to a laser irradiation resistant coating composition and a coating preparation method. Background Art
[0002] Laser technology is widely used in aerospace, medicine, industrial manufacturing and other fields. With the substantial increase in laser power, high-energy lasers can melt and damage traditional structural materials in a short period of time. Therefore, how to resist radiation damage from high-energy lasers has become an extremely challenging task.
[0003] During the laser irradiation process, part of the laser energy is dissipated in the form of reflection when it contacts the material, and the remaining part of the laser energy is converted from light to heat on the surface of the material and deposited on the surface of the material in the form of heat, forming a local high-temperature area and causing the material to melt and gasify and other damage and failure behaviors. Coating a layer of laser protective coating on the surface of the material is an effective means of protection. The existing coatings of this type are mainly reflective protective coatings or ablative heat-insulating protective coatings. The former mainly relies on the high reflectivity of the coating to reduce the absorption ratio of laser energy and play a protective role. Although this type of coating has the advantage of being reusable and has a long protection time, it is easy to cause the coating to fail due to the appearance of bad spots when facing high-power laser irradiation; the latter mainly relies on the ablation energy consumption and heat insulation characteristics of the material to dissipate and isolate the heat generated by the laser to prevent high temperature from damaging the base material. Although this type of coating can better resist the short-term ablation of high-power lasers, the surface has a high light absorption ratio, resulting in a short coating protection time.
[0004] From the above analysis, it can be seen that the currently developed reflective protective coatings and ablative thermal insulation protective coatings each have their own advantages and disadvantages. However, with the development of high-energy laser technology, a single protection mechanism has been difficult to meet the gradually increasing protection indicators. How to effectively combine multiple protection mechanisms to further improve the protective performance of the coating is a key technical problem that needs to be solved at present. Summary of the invention
[0005] The present disclosure provides a laser irradiation resistant coating composition and a coating preparation method, which can effectively solve the above problems.
[0006] The present disclosure is implemented as follows:
[0007] In one aspect, the present disclosure provides a laser radiation resistant coating composition, the coating composition comprising a heat-insulating layer composition, a lateral heat-dissipating layer composition, and a reflective layer composition;
[0008] Wherein, the thermal insulation layer composition comprises the following components in parts by mass:
[0009] 60-65 parts of film-forming resin, 17.5-20 parts of ceramic particles, and 17.5-20 parts of ceramic hollow balls;
[0010] The lateral heat dissipation layer composition comprises the following components in parts by mass:
[0011] 90-95 parts of film-forming resin, 5-10 parts of high thermal conductivity boride;
[0012] The reflective layer composition comprises the following components in parts by weight:
[0013] 58-65 parts of film-forming resin, 30-39 parts of ceramic particles, and 3-5 parts of chopped fibers.
[0014] In another aspect, the present disclosure provides a method for preparing a laser radiation resistant coating, the method comprising:
[0015] Weighing a film-forming resin, ceramic particles and ceramic hollow balls according to a mass ratio, adding the ceramic particles and ceramic hollow balls to the film-forming resin, and dispersing them evenly to obtain a first coating slurry, applying the first coating slurry to a substrate surface, and then pre-curing to obtain a first substrate;
[0016] Weighing a film-forming resin and a high thermal conductivity boride according to a mass ratio, adding the high thermal conductivity boride to the film-forming resin, and evenly dispersing the boride to obtain a second coating slurry, applying the second coating slurry to the surface of the first substrate, and then pre-curing to obtain a second substrate;
[0017] The film-forming resin, ceramic particles and chopped fibers are weighed according to the mass ratio, the ceramic particles and chopped fibers are added to the film-forming resin, and dispersed evenly to obtain a third coating slurry, the third coating slurry is applied to the surface of the second substrate, and then cured to obtain a laser radiation resistant coating.
[0018] The beneficial effects of the present disclosure are:
[0019] The present disclosure provides a laser radiation resistant coating composition, wherein the prepared coating comprises a three-layer structure, wherein a heat insulation layer, a lateral heat dissipation layer and a reflective layer are sequentially distributed from the inside to the outside of the substrate surface. The heat insulation layer has a low thermal conductivity and can provide a good heat insulation effect; the high thermal conductivity material of the lateral heat dissipation layer enables the layer to have a good lateral thermal conductivity, effectively ensuring that the local high temperature can be quickly evacuated to the surrounding area to prevent the generation of ultra-high temperature in the center; the reflective layer has a high melting point and reflectivity, achieving high reflective properties of the coating. Based on the synergistic coordination of the above-mentioned reflection, lateral heat dissipation and heat insulation, the coating has good resistance to high-energy laser radiation.
[0020] Furthermore, the present disclosure provides a method for preparing the coating, which is simple and easy, has low cost, can meet the requirements of large-scale preparation, and can be applied to the surface of materials that may be exposed to high-energy laser irradiation to avoid damage. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0022] Figure 1 This is a macroscopic morphology of the laser radiation resistant coating prepared in Example 1 of the present disclosure.
[0023] Figure 2 The laser irradiation resistant coating prepared in Example 1 of the present disclosure is subjected to a power density of 500 W / cm 2 Macroscopic morphology after 20s of laser irradiation.
[0024] Figure 3 The laser irradiation resistant coating prepared in Example 1 of the present disclosure is subjected to a power density of 500 W / cm 2 Back temperature curve of aluminum alloy plate substrate after 20s of laser irradiation.
[0025] Figure 4 The laser irradiation resistant coating prepared in Example 2 of the present disclosure was subjected to a power density of 1000 W / cm 2 Back temperature curve of aluminum alloy plate substrate after 10s of laser irradiation.
[0026] Figure 5 The laser irradiation resistant coating prepared in Example 5 of the present disclosure is subjected to a power density of 500 W / cm 2 Back temperature curve of aluminum alloy plate substrate after 20s of laser irradiation.
[0027] Figure 6 The laser irradiation resistant coating prepared in Example 6 of the present disclosure was subjected to a power density of 500 W / cm 2 Back temperature curve of aluminum alloy plate substrate after 20s of laser irradiation. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the embodiments of the present disclosure clearer, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present disclosure. Therefore, the following detailed description of the embodiments of the present disclosure provided in the drawings is not intended to limit the scope of the present disclosure for protection, but merely represents the selected embodiments of the present disclosure. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present disclosure.
[0029] An embodiment of the present disclosure provides a laser radiation resistant coating, which is disposed on the surface of a substrate. From the surface of the substrate outward, the coating is sequentially provided with a heat insulation layer, a lateral heat dissipation layer and a reflective layer.
[0030] Wherein, the thermal insulation layer comprises the following components in parts by mass:
[0031] 60-65 parts of film-forming resin, 17.5-20 parts of ceramic particles, and 17.5-20 parts of ceramic hollow spheres.
[0032] The film-forming resin, as the basic component of the three-layer structure, can bond the components contained in each layer together to form an overall uniform layer structure, providing the layer structure with certain mechanical properties and chemical stability, especially as an anti-laser radiation coating, which needs to exhibit good performance under high temperature conditions.
[0033] At the same time, the film-forming resin can also generate good adhesion with the base coat or substrate through chemical bonding.
[0034] In some embodiments, the film-forming resin is a thermosetting resin having a solid content greater than 50% at 900° C.
[0035] The film-forming resin has a high solid content, which ensures that under the conditions of high-energy laser action, a high proportion of residual resin matter can effectively shield the laser and prevent the coating from being directly penetrated.
[0036] The use of thermosetting resins enables pre-curing of the layer structure and final curing to obtain a structurally stable coating with predetermined properties.
[0037] In some embodiments, the film-forming resin is a silicone resin.
[0038] The thermal insulation layer is made of a mixture of ceramic particles and ceramic hollow balls. Both materials are high melting point materials with low thermal conductivity. Adding an appropriate amount of ceramic hollow balls can further reduce the overall density and thermal conductivity of the mixture through their hollow structure, thereby achieving better thermal insulation effect.
[0039] When the amount of ceramic hollow balls is too low, it is not possible to effectively block the transfer of the remaining heat to the substrate. When the amount of ceramic hollow balls is too high, it will affect the overall mechanical strength of the mixture, especially the thermal insulation layer as the internal layer structure of the coating, which needs to support the two outer layer structures. If the mechanical strength is not enough, it is easy to break when subjected to external force, thus affecting the overall strength of the coating. Moreover, too many hollow structures will lead to excessive air content in the thermal insulation layer structure, thereby affecting the thermal stability of the thermal insulation layer, causing it to deform or break at high temperatures, thereby affecting the thermal insulation performance and service life of the coating.
[0040] In some embodiments, the ceramic particles are high melting point metal oxides, for example, the ceramic particles are aluminum oxide powder or zirconium oxide powder.
[0041] Furthermore, in some embodiments, the particle size of the ceramic particles is 35 μm-75 μm. If the particle size is too large, the particles will easily settle; if the particle size is too small, the particles will easily agglomerate. Therefore, if the particle size is too large or too small, the dispersion of the ceramic particles in the coating will be affected.
[0042] In some embodiments, the ceramic hollow spheres are alumina hollow spheres.
[0043] Furthermore, in some embodiments, the particle size of the ceramic hollow sphere is 0.2 mm to 0.4 mm. A hollow sphere with a particle size that is too small has poor thermal insulation performance; a hollow sphere with a particle size that is too large will cause particle sedimentation and affect dispersion.
[0044] Furthermore, the pore size of the ceramic hollow sphere is 0.1-0.25 mm.
[0045] The lateral heat dissipation layer comprises the following components in parts by mass:
[0046] 90-95 parts of film-forming resin and 5-10 parts of high thermal conductivity boride.
[0047] In the lateral heat dissipation layer, the use of the above mass fraction of high thermal conductivity boride can achieve excellent lateral thermal conductivity, and transfer the heat in the vertical direction to the horizontal direction during the laser ablation of the material. If too little mass fraction is used, a good effect cannot be achieved. If the amount used exceeds this range, the effect is not significantly improved and the cost is increased.
[0048] In some embodiments, the high thermal conductivity boride is hexagonal boron nitride.
[0049] Hexagonal boron nitride is highly anisotropic, and its in-plane thermal conductivity is much higher than the thermal conductivity perpendicular to the plane. The reported experimental value of the in-plane thermal conductivity of hexagonal boron nitride can reach 220-420 W / m·K at room temperature.
[0050] Furthermore, in some embodiments, the particle size of the high thermal conductive boride is 1 μm-2 μm.
[0051] The reflective layer comprises the following components in parts by weight:
[0052] 58-65 parts of film-forming resin, 30-39 parts of ceramic particles, and 3-5 parts of chopped fibers.
[0053] The ceramic particles have a high melting point and a high reflectivity, which can realize the high reflection energy dissipation characteristics of the layer structure.
[0054] Using smaller ceramic particles can increase the surface area of the material, thereby improving its reflective effect.
[0055] The addition of chopped fibers is used to achieve a toughening effect, thereby reducing cracks in the ablated area of the reflective layer after high-energy laser ablation.
[0056] In some embodiments, the chopped fibers are loose zirconia fibers.
[0057] Zirconia fiber bulk wool is widely used in high temperature insulation due to its high temperature resistance and low thermal conductivity. When used as a reflective layer, zirconia fiber bulk wool can provide the following advantages:
[0058] 1. High temperature stability: Zirconia fiber bulk wool can be used in environments up to 2200°C, which makes it ideal for high temperature reflective layer applications.
[0059] 2. Low thermal conductivity: At 1400°C, the thermal conductivity of zirconia fiber bulk wool is less than 0.1, which helps to reduce heat transfer and improve the thermal insulation effect of the reflective layer.
[0060] Furthermore, in some embodiments, the line diameter of the chopped fibers is 30 nm-50 nm.
[0061] Optimizing the line diameter of the chopped fibers helps them form a uniform heat-insulating and reflective barrier in the reflective layer.
[0062] In some embodiments, the coating has a thickness of 1000 μm-2000 μm.
[0063] In some embodiments, the thickness of the thermal insulation layer is 350 μm-700 μm;
[0064] The thickness of the lateral heat dissipation layer is 350 μm-700 μm;
[0065] The thickness of the reflective layer is 350 μm-700 μm.
[0066] The thickness of each layer structure is selected based on the properties of the respective materials and the expected application effect, so as to achieve a balance between the overall high efficiency of the coating in resisting laser radiation and economical practicality.
[0067] In some embodiments, the material of the matrix is one of pure metal, alloy, and resin-based composite material.
[0068] The coating can have a wider range of substrate applications, be compatible with a variety of substrates, and achieve expected performance.
[0069] An embodiment of the present invention provides a method for preparing a laser radiation resistant coating, the method comprising:
[0070] Weighing a film-forming resin, ceramic particles and ceramic hollow balls according to a mass ratio, adding the ceramic particles and ceramic hollow balls to the film-forming resin, and dispersing them evenly to obtain a first coating slurry, applying the first coating slurry to a substrate surface, and then pre-curing to obtain a first substrate;
[0071] Weighing a film-forming resin and a high thermal conductivity boride according to a mass ratio, adding the high thermal conductivity boride to the film-forming resin, and evenly dispersing the boride to obtain a second coating slurry, applying the second coating slurry to the surface of the first substrate, and then pre-curing to obtain a second substrate;
[0072] The film-forming resin, ceramic particles and chopped fibers are weighed according to the mass ratio, the ceramic particles and chopped fibers are added to the film-forming resin, and dispersed evenly to obtain a third coating slurry, the third coating slurry is applied to the surface of the second substrate, and then cured to obtain a laser radiation resistant coating.
[0073] In some embodiments, the method further comprises:
[0074] The surface of the substrate is roughened and then cleaned to remove dust and oil impurities attached to the surface of the substrate.
[0075] This step can improve the adhesion of the coating on the substrate.
[0076] In some embodiments, the surface of the substrate is roughened by using 400-800 grit sandpaper to grind the surface of the substrate material so that the scratches are evenly distributed over the entire surface of the substrate.
[0077] In some embodiments, the uniform dispersion comprises:
[0078] Stir at a speed of 500r / min-800r / min for 15min-40min, then homogenize at a homogenization frequency of 1500r / min-2000r / min for 15min-30min, and then stir at a speed of 500r / min-800r / min for 10min-30min.
[0079] The process consists of two main steps: stirring and homogenizing. The purpose of this process is to ensure that the various ingredients in the slurry are fully mixed and evenly dispersed, which is crucial to obtain a layer structure with consistent properties.
[0080] Among them, the initial stirring is carried out at a lower speed to initially mix the solids and film-forming resin in the slurry to form a relatively uniform mixture. The stirring speed at this stage should not be too fast to avoid generating too many bubbles. The homogenization treatment is carried out at a higher homogenization frequency to further reduce the aggregation of a single component and improve the uniformity and stability of the slurry. The high shear force during the homogenization process helps to destroy the agglomeration phenomenon and achieve the dispersion of each component.
[0081] After homogenization, stirring is performed again at a lower speed to remove air bubbles that may have been generated during the homogenization process. Stirring at this stage also helps adjust the viscosity of the slurry to make it more suitable for the coating process.
[0082] In some embodiments, curing is performed, comprising:
[0083] Keep warm at 70℃-80℃ for 4h-6h, 100℃-110℃ for 2h-3h, 120℃-130℃ for 2h-3h, 150℃-160℃ for 2h-3h and 200℃-210℃ for 1h-1.5h.
[0084] The purpose of this process is to ensure that the material cures evenly and thoroughly while avoiding degradation of material properties or structural damage due to rapid temperature changes.
[0085] Among them, starting the curing process at a lower temperature can help the material gradually lose moisture and volatile components, and at the same time start the initial chemical cross-linking reaction. Gradually increasing the temperature will help complete the curing reaction, improve the thermal stability and mechanical properties of the material, and also help eliminate the residual stress inside the material.
[0086] The information of raw materials and instruments in the following examples is shown in Table 1.
[0087] Table 1 Information of raw materials and instruments
[0088]
[0089] Example 1
[0090] A multi-effect synergistic high-energy laser irradiation resistant coating is provided on the surface of a substrate, and from the surface of the substrate outwards, the coating is sequentially provided with a heat insulation layer, a lateral heat dissipation layer and a reflection layer.
[0091] The total mass of the raw materials used to prepare each layer structure is taken as 100%.
[0092] The mass fractions of the components in the thermal insulation layer are: 65% of organic silicon resin, 17.5% of solid aluminum oxide particles, and 17.5% of hollow aluminum oxide microspheres.
[0093] The mass fractions of the components in the lateral heat dissipation layer are: 95% silicone resin and 5% hexagonal boron nitride.
[0094] The mass fractions of the components in the reflective layer are: 65% of organic silicon resin, 30% of solid aluminum oxide particles, and 5% of chopped zirconium oxide fibers.
[0095] The preparation method of the high-energy laser irradiation resistant coating is as follows:
[0096] Step 1: First, polish the surface of the aluminum alloy with 400-grit sandpaper until the scratches cover the entire surface of the substrate, and then clean the surface of the aluminum alloy plate with acetone.
[0097] Step 2, add 17.5g of alumina solid particles and 17.5g of alumina hollow microspheres to 65g of silicone resin, and stir with an overhead stirrer at a speed of 500r / min for 40min, then homogenize in a homogenizer with a homogenization frequency set to 1500r / min for 30min, and then continue to stir at a speed of 500r / min for 30min to obtain a uniformly dispersed first coating slurry.
[0098] The first coating slurry is coated on the surface of the aluminum alloy plate by a coating machine, and the coating thickness of the coating machine is set to 500 μm. After coating, the aluminum alloy plate is placed in a 40° C. oven for pre-curing for 3 hours to obtain the first thermal insulation layer of the coating.
[0099] Step 3, add 5g of hexagonal boron nitride nanosheets to 95g of silicone resin, and stir with an overhead stirrer at a speed of 500r / min for 40min, then homogenize in a homogenizer with a homogenization frequency set to 1500r / min for 30min, and then continue to stir at a speed of 500r / min for 30min to obtain a uniformly dispersed second coating slurry.
[0100] The second coating slurry is coated on the surface of the above-mentioned thermal insulation layer by a coating machine, and the coating thickness of the coating machine is set to 500 μm. After coating, the aluminum alloy plate is placed in a 40° C. oven for pre-curing for 3 hours to obtain a second lateral heat dissipation layer of the coating.
[0101] Step 4, add 30g of solid alumina particles and 5g of loose zirconium oxide fibers to 65g of silicone resin, and stir at a speed of 500r / min using an overhead stirrer for 40min, then homogenize in a homogenizer with a homogenization frequency set to 1500r / min for 30min, and then continue stirring at a speed of 500r / min for 30min to obtain a uniformly dispersed third coating slurry.
[0102] The third coating slurry is coated on the surface of the above-mentioned transverse heat dissipation layer by a coater, and the coating thickness of the coater is set to 500 μm. After coating, the aluminum alloy plate is placed in a 40° C. oven for pre-curing for 3 hours to obtain the third reflective layer of the coating.
[0103] Step 5, after the aluminum alloy plate is coated three times, the aluminum alloy plate is placed in an oven for heat preservation and curing. First, it is kept at 70°C for 4 hours, then kept at 100°C, 120°C, and 150°C for 2 hours, and finally kept at 200°C for 1 hour to obtain the high-energy laser irradiation resistant coating with a thickness of 1500 μm. The macroscopic morphology of the coating is as follows: Figure 1 shown.
[0104] Test Example 1
[0105] The power density is 500W / cm 2 The high-energy laser irradiation resistant coating prepared in Example 1 was irradiated with a high-energy laser (beam spot diameter 10 mm) for 20 seconds. The macroscopic morphology of the coating is as follows: Figure 2 As shown, obvious ablation marks can be observed in the irradiated area.
[0106] After high-energy laser ablation, there was no damage to the coating due to large-scale particle peeling around the ablation area due to high-temperature thermal expansion and cooling contraction, indicating that the addition of zirconia fiber loose wool in the reflective layer successfully enhanced the toughness of the coating.
[0107] The size of the ablation area of the coating after irradiation has increased significantly compared to the laser beam spot size. The reason for this is the presence of hexagonal boron nitride nanosheets in the lateral heat dissipation layer, which has excellent lateral thermal conductivity. This fully demonstrates that the hexagonal boron nitride nanosheets are relatively successful in transferring heat from the vertical direction to the horizontal direction during the ablation process.
[0108] The back surface temperature of the aluminum alloy plate during irradiation was monitored in real time using a K-type thermocouple to obtain the back temperature curve of the aluminum alloy plate, as shown in Figure 3As shown in the figure, it can be seen that the highest temperature of the aluminum alloy plate is 80.2°C, which means that the hollow alumina balls in the thermal insulation layer effectively block the transfer of the remaining heat to the substrate after lateral transfer, thereby effectively reducing the back surface temperature.
[0109] Figure 3 It can be proved that the coating has excellent resistance to high-energy laser irradiation.
[0110] Example 2
[0111] A multi-effect synergistic high-energy laser irradiation resistant coating is provided on the surface of a substrate, and from the surface of the substrate outwards, the coating is sequentially provided with a heat insulation layer, a lateral heat dissipation layer and a reflection layer.
[0112] The total mass of the raw materials used to prepare each layer structure is taken as 100%.
[0113] The mass fractions of the components in the thermal insulation layer are: 63% of organic silicon resin, 18.5% of solid aluminum oxide particles, and 18.5% of hollow aluminum oxide microspheres.
[0114] The mass fractions of the components in the lateral heat dissipation layer are: 92% silicone resin and 8% hexagonal boron nitride.
[0115] The mass fractions of the components in the reflective layer are: 61% of organic silicone resin, 34.5% of solid aluminum oxide particles, and 4.5% of chopped zirconium oxide fibers.
[0116] The preparation method of the high-energy laser irradiation resistant coating is as follows:
[0117] Step 1: First, polish the surface of the aluminum alloy with 600-grit sandpaper until the scratches cover the entire surface of the substrate, and then clean the surface of the aluminum alloy plate with acetone.
[0118] Step 2, add 18.5g of alumina solid particles and 18.5g of alumina hollow microspheres to 63g of silicone resin, and stir with an overhead stirrer at a speed of 600r / min for 25min, then homogenize in a homogenizer with a homogenization frequency set to 1800r / min for 20min, and then continue to stir at a speed of 600r / min for 20min to obtain a uniformly dispersed first coating slurry.
[0119] The first coating slurry was coated on the surface of the aluminum alloy plate by a coating machine, and the coating thickness of the coating machine was set to 650 μm. After coating, the aluminum alloy plate was placed in a 50° C. oven for pre-curing for 2.5 hours to obtain the first thermal insulation layer of the coating.
[0120] Step 3, add 8 g of hexagonal boron nitride nanosheets to 92 g of silicone resin, and stir with an overhead stirrer at a speed of 600 r / min for 25 min, then homogenize in a homogenizer with a homogenization frequency set to 1800 r / min for 20 min, and then continue to stir at a speed of 600 r / min for 20 min to obtain a uniformly dispersed second coating slurry.
[0121] The second coating slurry was coated onto the surface of the thermal insulation layer by a coating machine, and the coating thickness of the coating machine was set to 650 μm. After coating, the aluminum alloy plate was placed in a 50° C. oven for pre-curing for 2.5 hours to obtain a second lateral heat dissipation layer of the coating.
[0122] Step 4, add 34.5g of solid alumina particles and 4.5g of loose zirconium oxide fibers to 61g of silicone resin, and stir with an overhead stirrer at a speed of 600r / min for 25min, then homogenize in a homogenizer with a homogenization frequency set to 1800r / min for 20min, and then continue stirring at a speed of 600r / min for 20min to obtain a uniformly dispersed third coating slurry.
[0123] The third coating slurry is coated on the surface of the above-mentioned transverse heat dissipation layer by a coater, and the coating thickness of the coater is set to 650 μm. After coating, the aluminum alloy plate is placed in a 50° C. oven for pre-curing for 2.5 hours to obtain the third reflective layer of the coating.
[0124] Step 5, after the aluminum alloy plate is coated three times, the aluminum alloy plate is placed in an oven for heat preservation and curing. First, it is kept at 70°C for 4 hours, then kept at 100°C, 120°C, and 150°C for 2 hours, and finally kept at 200°C for 1 hour, to obtain the high-energy laser irradiation resistant coating with a thickness of 1950 μm.
[0125] Test Example 2
[0126] The power density is 1000W / cm 2 The high-energy laser irradiation resistant coating prepared in Example 2 was irradiated with a laser (beam spot diameter 10 mm) for 10 seconds, and a K-type thermocouple was used to monitor the back surface temperature of the aluminum alloy plate in real time during the irradiation process to obtain a back temperature curve of the aluminum alloy plate, as shown in FIG. Figure 4 As shown, it can be seen from the figure that the highest temperature of the aluminum alloy plate is 125.7℃.
[0127] Figure 4 It can be proved that the coating has excellent resistance to high-energy laser irradiation.
[0128] Example 3
[0129] A multi-effect synergistic high-energy laser irradiation resistant coating is provided on the surface of a substrate, and from the surface of the substrate outwards, the coating is sequentially provided with a heat insulation layer, a lateral heat dissipation layer and a reflection layer.
[0130] The total mass of the raw materials used to prepare each layer structure is taken as 100%.
[0131] The mass fractions of the components in the thermal insulation layer are: 62% of organic silicon resin, 19% of solid aluminum oxide particles, and 19% of hollow aluminum oxide microspheres.
[0132] The mass fractions of the components in the lateral heat dissipation layer are: 93.5% of silicone resin and 6.5% of hexagonal boron nitride.
[0133] The mass fractions of the components in the reflective layer are: 60% of organic silicon resin, 36% of solid aluminum oxide particles, and 4% of chopped zirconium oxide fibers.
[0134] The preparation method of the high-energy laser irradiation resistant coating is as follows:
[0135] Step 1: First, polish the surface of the aluminum alloy with 800-grit sandpaper until the scratches cover the entire surface of the substrate, and then clean the surface of the aluminum alloy plate with acetone.
[0136] Step 2: Add 19 g of alumina solid particles and 19 g of alumina hollow microspheres to 62 g of silicone resin, stir for 20 min at 700 r / min using an overhead stirrer, then homogenize for 15 min in a homogenizer with a homogenization frequency set to 2000 r / min, and continue stirring at 700 r / min for 15 min to obtain a uniformly dispersed first coating slurry.
[0137] The first coating slurry was coated on the surface of the aluminum alloy plate by a coating machine, and the coating thickness of the coating machine was set to 550 μm. After coating, the aluminum alloy plate was placed in a 45° C. oven for pre-curing for 3 hours to obtain the first thermal insulation layer of the coating.
[0138] Step 3, add 6.5 g of hexagonal boron nitride nanosheets to 93.5 g of silicone resin, and stir with an overhead stirrer at a speed of 700 r / min for 20 min, then homogenize in a homogenizer with a homogenization frequency set to 2000 r / min for 15 min, and then continue to stir at a speed of 700 r / min for 15 min to obtain a uniformly dispersed second coating slurry.
[0139] The second coating slurry is coated on the surface of the above-mentioned thermal insulation layer by a coating machine, and the coating thickness of the coating machine is set to 550 μm. After coating, the aluminum alloy plate is placed in a 45° C. oven for pre-curing for 3 hours to obtain the second lateral heat dissipation layer of the coating.
[0140] Step 4, add 36g of solid alumina particles and 4g of loose zirconium oxide fibers to 60g of silicone resin, and stir with an overhead stirrer at a speed of 700r / min for 20min, then homogenize in a homogenizer with a homogenization frequency set to 2000r / min for 15min, and then continue stirring at a speed of 700r / min for 15min to obtain a uniformly dispersed third coating slurry.
[0141] The third coating slurry is coated on the surface of the above-mentioned transverse heat dissipation layer by a coater, and the coating thickness of the coater is set to 550 μm. After coating, the aluminum alloy plate is placed in a 45° C. oven for pre-curing for 3 hours to obtain the third reflective layer of the coating.
[0142] Step 5, after the aluminum alloy plate surface is coated three times, the aluminum alloy plate is placed in an oven for heat preservation and curing. First, it is kept at 70°C for 6 hours, then kept at 100°C, 120°C, and 150°C for 2 hours, and finally kept at 200°C for 1 hour, to obtain the high-energy laser irradiation resistant coating with a thickness of 1650 μm.
[0143] Example 4
[0144] A multi-effect synergistic high-energy laser irradiation resistant coating is provided on the surface of a substrate, and from the surface of the substrate outwards, the coating is sequentially provided with a heat insulation layer, a lateral heat dissipation layer and a reflection layer.
[0145] The total mass of the raw materials used to prepare each layer structure is taken as 100%.
[0146] The mass fractions of the components in the heat insulation layer are: 60% of organic silicon resin, 20% of solid aluminum oxide particles, and 20% of hollow aluminum oxide microspheres.
[0147] The mass fractions of the components in the lateral heat dissipation layer are: 90% silicone resin and 10% hexagonal boron nitride.
[0148] The mass fractions of the components in the reflective layer are: 58% organic silicon resin, 39% alumina solid particles, and 3% zirconia chopped fibers.
[0149] The preparation method of the high-energy laser irradiation resistant coating is as follows:
[0150] Step 1: First, polish the surface of the aluminum alloy with 600-grit sandpaper until the scratches cover the entire surface of the substrate, and then clean the surface of the aluminum alloy plate with acetone.
[0151] Step 2: Add 20 g of alumina solid particles and 20 g of alumina hollow microspheres to 60 g of silicone resin, stir for 15 min at 800 r / min using an overhead stirrer, then homogenize for 15 min in a homogenizer with a homogenization frequency set to 2000 r / min, and then continue stirring at 800 r / min for 10 min to obtain a uniformly dispersed first coating slurry.
[0152] The first coating slurry is coated on the surface of the aluminum alloy plate by a coating machine, and the coating thickness of the coating machine is set to 600 μm. After coating, the aluminum alloy plate is placed in a 30° C. oven for pre-curing for 4 hours to obtain the first thermal insulation layer of the coating.
[0153] Step 3, add 10g of hexagonal boron nitride nanosheets to 90g of silicone resin, and stir with an overhead stirrer at a speed of 800r / min for 15min, then homogenize in a homogenizer with a homogenization frequency set to 2000r / min for 15min, and then continue to stir at a speed of 800r / min for 10min to obtain a uniformly dispersed second coating slurry.
[0154] The second coating slurry is coated on the surface of the above-mentioned thermal insulation layer by a coating machine, and the coating thickness of the coating machine is set to 600 μm. After coating, the aluminum alloy plate is placed in a 30° C. oven for pre-curing for 4 hours to obtain the second lateral heat dissipation layer of the coating.
[0155] Step 4, add 39g of solid alumina particles and 8g of loose zirconium oxide fibers to 59g of silicone resin, and stir with an overhead stirrer at a speed of 800r / min for 15min, then homogenize in a homogenizer with a homogenization frequency set to 2000r / min for 15min, and then continue stirring at a speed of 800r / min for 10min to obtain a uniformly dispersed third coating slurry.
[0156] The third coating slurry is coated on the surface of the above-mentioned transverse heat dissipation layer by a coater, and the coating thickness of the coater is set to 600 μm. After coating, the aluminum alloy plate is placed in a 30° C. oven for pre-curing for 4 hours to obtain the third reflective layer of the coating.
[0157] Step 5, after the aluminum alloy plate surface is coated three times, the aluminum alloy plate is placed in an oven for heat preservation and curing. First, it is kept at 70°C for 6 hours, then kept at 100°C, 120°C, and 150°C for 2 hours, and finally kept at 200°C for 1 hour, to obtain the high-energy laser irradiation resistant coating with a thickness of 1800 μm.
[0158] Example 5
[0159] A high-energy laser irradiation resistant coating is provided on the surface of a substrate, and from the surface of the substrate outward, the coating is only prepared as a reflection layer.
[0160] The total mass of the raw materials used to prepare each layer structure is taken as 100%.
[0161] The mass fractions of the components in the reflective layer are: 65% organic silicon resin, 30% alumina solid particles, and 5% zirconium oxide chopped fibers.
[0162] The preparation method of the high-energy laser irradiation resistant coating is as follows:
[0163] Step 1: First, polish the surface of the aluminum alloy with 400-grit sandpaper until the scratches cover the entire surface of the substrate, and then clean the surface of the aluminum alloy plate with acetone.
[0164] Step 2: Add 30 g of solid alumina particles and 5 g of loose zirconium oxide fibers to 65 g of silicone resin, stir at 500 r / min for 40 min using an overhead stirrer, then homogenize in a homogenizer with a homogenization frequency set to 1500 r / min for 30 min, and continue stirring at 500 r / min for 30 min to obtain a uniformly dispersed coating slurry.
[0165] The coating slurry is coated on the surface of the aluminum alloy plate by a coating machine, and the coating thickness of the coating machine is set to 1500 μm. After coating, the aluminum alloy plate is placed in a 40° C. oven for pre-curing for 3 hours to obtain a pre-cured anti-laser radiation coating.
[0166] Step 3: After the coating is completed on the surface of the aluminum alloy plate, the aluminum alloy plate is placed in an oven for heat preservation and curing. First, it is kept at 70°C for 4 hours, then kept at 100°C, 120°C, and 150°C for 2 hours, and finally kept at 200°C for 1 hour to obtain a reflective high-energy laser irradiation resistant coating with a thickness of 1500 μm.
[0167] Test Example 3
[0168] The power density is 500W / cm 2 The high-energy laser irradiation resistant coating prepared in Example 5 was irradiated with a laser (beam spot diameter 10 mm) for 20 seconds, and a K-type thermocouple was used to monitor the back surface temperature of the aluminum alloy plate in real time during the irradiation process to obtain a back temperature curve of the aluminum alloy plate, as shown in FIG. Figure 5 As shown, it can be seen from the figure that the highest temperature of the aluminum alloy plate is 178.4℃.
[0169] Figure 3 and Figure 5By comparison, it can be proved that under the conditions of the same laser parameters and coating thickness, the reflection-lateral heat dissipation-thermal insulation composite coating can reduce the maximum temperature of the aluminum alloy plate substrate. Therefore, the laser protection performance of the reflection-lateral heat dissipation-thermal insulation composite coating is better than that of the single reflective protective coating.
[0170] Example 6
[0171] A multi-effect synergistic high-energy laser irradiation resistant coating is provided on the surface of a substrate, and a heat insulation layer and a reflection layer are sequentially distributed on the coating from the surface of the substrate outward.
[0172] The total mass of the raw materials used to prepare each layer structure is taken as 100%.
[0173] The mass fractions of the components in the heat insulation layer are: 65% organic silicon resin, 17.5% solid aluminum oxide particles, and 17.5% hollow aluminum oxide microspheres.
[0174] The mass fractions of the components in the reflective layer are: 65% organic silicon resin, 30% alumina solid particles, and 5% zirconium oxide chopped fibers.
[0175] The preparation method of the high-energy laser irradiation resistant coating is as follows:
[0176] Step 1: First, polish the surface of the aluminum alloy with 400-grit sandpaper until the scratches cover the entire surface of the substrate, and then clean the surface of the aluminum alloy plate with acetone.
[0177] Step 2, add 17.5g of alumina solid particles and 17.5g of alumina hollow microspheres to 65g of silicone resin, and stir with an overhead stirrer at a speed of 500r / min for 40min, then homogenize in a homogenizer with a homogenization frequency set to 1500r / min for 30min, and then continue to stir at a speed of 500r / min for 30min to obtain a uniformly dispersed first coating slurry.
[0178] The first coating slurry is coated on the surface of the aluminum alloy plate by a coating machine, and the coating thickness of the coating machine is set to 750 μm. After coating, the aluminum alloy plate is placed in a 40° C. oven for pre-curing for 3 hours to obtain the first thermal insulation layer of the coating.
[0179] Step 3, add 30g of solid alumina particles and 5g of loose zirconium oxide fibers to 65g of silicone resin, and stir at a speed of 500r / min using an overhead stirrer for 40min, then homogenize in a homogenizer with a homogenization frequency set to 1500r / min for 30min, and then continue stirring at a speed of 500r / min for 30min to obtain a uniformly dispersed second coating slurry.
[0180] The second coating slurry was coated onto the surface of the thermal insulation layer by a coating machine, and the coating thickness of the coating machine was set to 750 μm. After coating, the aluminum alloy plate was placed in an oven at 40° C. for pre-curing for 3 hours to obtain the second reflective layer of the coating.
[0181] Step 4: After the aluminum alloy plate is coated twice, the aluminum alloy plate is placed in an oven for heat preservation and curing. First, it is kept at 70°C for 4 hours, then kept at 100°C, 120°C, and 150°C for 2 hours, and finally kept at 200°C for 1 hour to obtain a reflective-insulating high-energy laser irradiation resistant coating with a thickness of 1500 μm.
[0182] Test Example 4
[0183] The power density is 500W / cm 2 The high-energy laser irradiation resistant coating prepared in Example 5 was irradiated with a laser (beam spot diameter 10 mm) for 20 seconds, and a K-type thermocouple was used to monitor the back surface temperature of the aluminum alloy plate in real time during the irradiation process to obtain a back temperature curve of the aluminum alloy plate, as shown in FIG. Figure 6 As shown, it can be seen from the figure that the highest temperature of the aluminum alloy plate is 125.3℃.
[0184] Figure 6 and Figure 5 By comparison, it can be proved that under the conditions of the same laser parameters, by adding a heat-insulating layer structure between the reflective protective coating and the substrate and adjusting the thickness of the reflective layer structure accordingly to achieve the same coating thickness, the obtained reflective-heat-insulating protective coating can reduce the maximum temperature of the aluminum alloy plate substrate. Therefore, the reflective-heat-insulating protective coating has better laser protection performance than the single reflective protective coating.
[0185] Figure 3 and Figure 6 By comparison, it can be proved that under the same laser parameter conditions, by adding a lateral heat dissipation layer structure between the reflective layer structure and the thermal insulation layer structure of the reflective-thermal insulation type protective coating, and adjusting the thickness of the reflective layer structure and the thermal insulation layer structure accordingly to achieve the same coating thickness, the obtained reflective-lateral heat dissipation-thermal insulation composite coating can reduce the maximum temperature of the aluminum alloy plate substrate. Therefore, the reflective-lateral heat dissipation-thermal insulation composite coating has better laser protection performance than the reflective-thermal insulation type protective coating.
[0186] In summary, the coating prepared by the coating composition provided in the embodiment of the present disclosure achieves the dissipation of laser energy and the isolation of laser deposited heat from the surface layer to the bottom layer through the synergistic effect of reflection, lateral heat dissipation and heat insulation, thereby achieving the purpose of resisting high-energy laser irradiation.
[0187] The coating preparation method is simple in process and low in cost, and the prepared coating has excellent protective performance.
[0188] The above description is only a preferred embodiment of the present disclosure and is not intended to limit the present disclosure. For those skilled in the art, the present disclosure may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.
Claims
1. A laser irradiation resistant coating composition, characterized in that: The coating composition comprises a heat-insulating layer composition, a lateral heat-dissipating layer composition and a reflective layer composition; Wherein, the thermal insulation layer composition comprises the following components in parts by mass: 60-65 parts of film-forming resin, 17.5-20 parts of ceramic particles, and 17.5-20 parts of ceramic hollow balls; The lateral heat dissipation layer composition comprises the following components in parts by mass: 90-95 parts of film-forming resin, 5-10 parts of high thermal conductivity boride; The reflective layer composition comprises the following components in parts by weight: The film-forming resin is 58 parts to 65 parts, the ceramic particles are 30 parts to 39 parts, and the zirconium oxide fiber bulk wool is 3 parts to 5 parts. The line diameter of the zirconium oxide fiber bulk wool is 30nm to 50nm.
2. The coating composition according to claim 1, characterized in that The film-forming resin is a thermosetting resin with a solid content greater than 50% at 900°C.
3. The coating composition according to claim 1, characterized in that The ceramic particles are aluminum oxide powder or zirconium oxide powder.
4. The coating composition according to claim 1, characterized in that The ceramic hollow sphere is an alumina hollow sphere.
5. The coating composition according to claim 1, characterized in that The high thermal conductivity boride is hexagonal boron nitride.
6. The coating composition according to claim 1, characterized in that The thickness of the thermal insulation layer is 350 μm-700 μm; The thickness of the lateral heat dissipation layer is 350 μm-700 μm; The thickness of the reflective layer is 350 μm-700 μm.
7. A method for preparing a laser-resistant coating using the laser-resistant coating composition according to any one of claims 1 to 6, characterized in that: The method comprises: Weighing a film-forming resin, ceramic particles and ceramic hollow balls according to a mass ratio, adding the ceramic particles and ceramic hollow balls to the film-forming resin, and dispersing them evenly to obtain a first coating slurry, applying the first coating slurry to a substrate surface, and then pre-curing to obtain a first substrate; Weighing a film-forming resin and a high thermal conductivity boride according to a mass ratio, adding the high thermal conductivity boride to the film-forming resin, and evenly dispersing the boride to obtain a second coating slurry, applying the second coating slurry to the surface of the first substrate, and then pre-curing to obtain a second substrate; The film-forming resin, ceramic particles and zirconia fiber loose wool are weighed according to the mass ratio, the ceramic particles and zirconia fiber loose wool are added to the film-forming resin, and dispersed evenly to obtain a third coating slurry, the third coating slurry is applied to the surface of the second substrate, and then cured to obtain a laser radiation resistant coating.
8. The method according to claim 7, characterized in that Curing is performed, including: Keep warm at 70℃-80℃ for 4h-6h, 100℃-110℃ for 2h-3h, 120℃-130℃ for 2h-3h, 150℃-160℃ for 2h-3h and 200℃-210℃ for 1h-1.5h.
9. The method according to claim 7, characterized in that: The material of the matrix is one of pure metal, alloy and resin-based composite material.
Citation Information
Patent Citations
Zirconium-boron-silicon laser protective coating and preparation method thereof
CN118406433A
Resin-based high-energy laser protective composite coating and preparation method thereof
CN118879190A